Integration of Agri-Tech tools among Malaysian women agripreneurs in sustainable farming - Abd Rashid, Nur Hidayah; Ismail, Nur Amalina; Bakar, Muhammad Aliuddin (Universiti Teknologi MARA, Terengganu, 2025)
This study investigates how Malaysian women agripreneurs adopt agricultural technology (Agri-Tech) to support sustainable farming practices. Despite agriculture contributing 8.4% to Malaysia's GDP and employing 16% of its workforce, women agripreneurs face significant adoption challenges, with Agri-Tech investments representing only 2.10% of the sector's digital expenditures. Through semi-structured interviews with 14 women agripreneurs who participated in the Department of Agriculture's training course, the study identified various Agri-Tech applications, including digital farm management systems, precision agriculture, and digital marketing platforms. Benefits included improved market access, resource optimisation, cost reduction, and environmental sustainability. However, barriers persisted: financial constraints, knowledge gaps, poor infrastructure, inadequate technical support, and unfavourable policies. Recommendations include targeted financial assistance, expanded digital training, improved rural connectivity, better technical support, and policy reforms prioritizing small-scale women agripreneurs. This research uniquely contributes to understanding gender-specific dimensions of Agri-Tech adoption in Southeast Asian agriculture. Future research should examine longitudinal impacts and policy effectiveness in addressing identified barriers.